Environmental studies of the Doce river basin in the pre and post-rupture context of the mining tailings dam - Carvalho, Raphaela Martins de; Gomes, Vanielle Aparecida do Patrocinio; Jankowsky, Mayra; Freitas, Rodrigo Randow de (Brazilian Journal of Production Engineering, 2021)
The Rio Doce Watershed is a complex mosaic of landscapes, a legacy of the geo-historical processes of occupation and exploitation of its natural resources. In this context, the greatest environmental impact recorded in this basin occurred in 2015, with the rupture of the tailings dam in Fundão, located in the municipality of Mariana - MG. Thus, this study aimed to develop a bibliometric analysis of publications related to fishing and aquaculture activity in the basin, with emphasis on environmental studies related to the biotic factors, in order to better understand how the themes changed in research and gaps in knowledge in the period before and after the disaster. For this, bibliometric methods were used in the general evaluation of articles and content analysis in articles related specifically to the biotic factors. As a result, there is an increase in the number of articles published after the disaster and the deepening of the vision of this scenario, as well as the greater interest of the international community in studying the area. Also, there is a change in the focus of the articles of the biotic factors, which starts to address primarily the impacts caused by tailings in the communities and their surroundings. In addition, there is a gap in the knowledge of the biotic factors in the region, mainly in the upper Rio Doce in the previous period and in the middle in the later. Thus, it is evident the importance of intensifying studies in this basin, aiming at the production of knowledge for a more sustainable management of its natural resources.
Keywords: Environmental impact; bibliometrics; biotic factors